2015
DOI: 10.1021/acsmacrolett.5b00541
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Miktoarm Branched Conjugated Copolymers by ROMPing In and Out

Abstract: Architecture represents an underutilized yet promising control element in polymer design due to the challenging synthesis of compositionally varied branched copolymers. We report the one-pot synthesis of miktoarm branched polymers by ring-opening metathesis polymerization. In this work, we graft to and from telechelic poly(3-hexylthiophene), which is end-capped by oxime click chemistry, using various norbornene monomers. The self-assembly of the resulting miktoarm H-shaped conjugated polymers is studied in sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 44 publications
1
28
0
1
Order By: Relevance
“…Table 2 summarizes the results for the preparation of the star ROMP polymers by Method 2 under a high CL/Mo ratio (CL/Mo = 20). The results also showed that the Mn values in the resultant ROMP polymers increased over the reaction time in the core formation (2nd step, runs [26][27][28][29][30][31][34][35][36][37], and the PDI values became low when the ROMPs were conducted under diluted conditions (Mw/Mn = 1.58-2.22, runs 34-37). However, the resultant polymers still possessed bimodal molecular weight distributions (runs [34][35][36][37].…”
Section: Synthesis Of Pyridine Modified Star-shaped Ring-opened Poly(mentioning
confidence: 90%
See 1 more Smart Citation
“…Table 2 summarizes the results for the preparation of the star ROMP polymers by Method 2 under a high CL/Mo ratio (CL/Mo = 20). The results also showed that the Mn values in the resultant ROMP polymers increased over the reaction time in the core formation (2nd step, runs [26][27][28][29][30][31][34][35][36][37], and the PDI values became low when the ROMPs were conducted under diluted conditions (Mw/Mn = 1.58-2.22, runs 34-37). However, the resultant polymers still possessed bimodal molecular weight distributions (runs [34][35][36][37].…”
Section: Synthesis Of Pyridine Modified Star-shaped Ring-opened Poly(mentioning
confidence: 90%
“…Star-shaped polymers consisting of linear arms connected at a central branched core are one of the simplest nonlinear polymers, and study for the precise synthesis by living polymerization technique attracts considerable attention [1][2][3][4][5][6][7]. Synthesis by adopting ring-opening metathesis polymerization (ROMP) [8][9][10][11][12][13][14][15][16] has been employed by sequential addition of monomers/cross linkers (CLs) [12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30], and the resultant polymers (soluble in organic solvent, such as toluene, chloroform, dichloromethane, etc.) were applied as fluorescent materials [19], supported catalysts [20], and as controlled release and drug delivery systems [24,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Given its mild-conditions, living nature, and exceptional functional group tolerance, ROMP of norbornene-based compounds has been widely used to generate functional materials for applications including resin technologies, biomedicine, catalysis, and sensing. [1][2][3][4][5][6][7] In addition, "graft-through" ROMP of norbornene-based macromonomers (MMs) that carry drug molecules, imaging agents, or diverse polymer sidechains has enabled rapid access to advanced polymer architectures for combination drug delivery, molecular imaging, and selfassembly. [8][9][10][11][12][13][14][15][16] Nevertheless, the lack of facile degradability of polynorbornene-based polymers is a key limitation (Figure 1a).…”
mentioning
confidence: 99%
“…18,19 Others subsequently showed that addition of small-molecule norbornene-based monomers to living star polymers prepared by arm-first ROMP enables the growth of new arms from the core, thus providing a new handle for tuning the star polymer functionality. 20–23 Such “in−out” processes have been demonstrated using other living polymerization techniques (e.g., ATRP 24–30 ) as well. Nonetheless, in the context of ROMP, these examples have invariably used small molecule monomers rather than MMs for the ROMP-in and ROMP-out steps.…”
mentioning
confidence: 87%